Expert Consensus on the Use of Teprotumumab for the Management of Thyroid Eye Disease Using a Modified-Delphi Approach. Issue 3 (24th September 2022) - Douglas, Raymond S.; Kossler, Andrea L.; Abrams, Jody; Briceño, Cesar A.; Gay, David; Harrison, Andrew; Lee, Michael; Nguyen, John; Joseph, Shannon S.; Schlachter, Dianne; Tan, Jeremy; Lynch, Judah; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Teprotumumab is the first treatment for thyroid eye disease (TED), a debilitating autoinflammatory condition, approved by the Food and Drug Administration in the United States, which reduces proptosis and improves quality of life. In the absence of guidelines, clinical recommendations were developed for using teprotumumab in patients with TED in the United States. Methods: A 3-round modified-Delphi panel was conducted between October 2020 and February 2021 with experts in the management of patients with TED. Key areas regarding the use of teprotumumab were investigated, including eligible patient populations, concomitant treatments, and assessment of response and adverse events. This used 2 survey rounds via an online questionnaire, where statements were scored using 9-point Likert scales. Statements with conflict were included in the third round, involving a consensus meeting via videoconference. Results: Consensus was obtained for all statements (n = 75); of which, 56% were revised to enable agreement of the group. The consensus meeting provided agreement regarding which populations should receive teprotumumab therapy, including all adult patients with TED with a clinical activity score of ≥4. Treatment with teprotumumab can also be considered for TED patients displaying the following characteristics: a CAS of <3, lid retraction of ≥2, and mild or early optic neuropathy with close clinical observation. Further recommendations included suitability of treatment for those beyond 16 months following the initial diagnosis of TED, low CAS concomitant treatment with steroids in some cases, retreatment for those who have relapses, and finally a recommendation to continue therapy for all 8 infusions despite the lack of response by the fourth infusion. Conclusions: This work constitutes the first consensus on guidelines for the use of teprotumumab. The modified Delphi approach involved physicians with significant experience with the clinical use of teprotumumab, and recommendations were based on current evidence.